Peste des Petits Ruminants risk factors and space–time clusters in Mymensingh, Bangladesh. Issue 6 (21st January 2017) - Rony, M. S.; Rahman, A. K. M. A.; Alam, M. M.; Dhand, N.; Ward, M. P.
Summary: Using a hospital‐based case–control study design, our aim was to identify risk factors for—and space–time clusters of—Peste des Petits Ruminants (PPR) in Mymensingh, Bangladesh. Three hundred and eighty PPR cases diagnosed between January 2005 and December 2014 at the Bangladesh Agricultural University Veterinary Teaching Hospital (BAUVTH) were selected; three controls per case from BAUVTH were then selected ( n = 1, 048). From records, data extracted included information on date of report, location, age, breed, sex and body weight of goats. A mixed multivariable logistic regression model was built to identify risk factors. Location was included as a random effect and season and demographic variables as fixed effects. The approximate geographic coordinates of locations were collected, and the scan statistic (Bernoulli model) was used to identify space–time clusters of PPR. Compared with goats <4 months of age, the odds of PPR were 3 (95% confidence interval [CI]: 1.95–4.66), 1.9 (CI: 1.34–2.76) and 1.8 times (95% CI: 1.19–2.58) greater in goats aged 4–6, >6–12 and >12–24 months, respectively. The occurrence of PPR was also significantly higher (odds ratio [OR] 3.2; 95% CI: 1.15–8.59) in the Jamunapari breed than Black Bengals. Significantly higher odds of PPR were observed in winter (OR 1.6; 95% CI: 1.06–2.14) and the monsoon season (OR 1.5; 95% CI: 1.04–2.11) compared with the post‐monsoon season. Two significant ( p < .05) space–time clusters were identified between 2 December 2006 and 6 September 2007 (two locations) and 28 November 2006 and 13 February 2007 (five locations). Peste des Petits Ruminants is endemic in Bangladesh, but also occurs as discrete outbreaks. Control efforts—such as vaccination—should focus on high‐risk groups (4–24 months of age, Jamunapari breed), prior to the onset of winter and the monsoon season so as to increase immunity during high‐risk periods, and focus on disease hotspots.